Stocking levels for lodgepole pine - Adams, David Lewis, author; Mogren, Edwin W., advisor; Fechner, Gilbert H., committee member; Remmenga, Elmer, committee member; Hays, Lloyd, committee member (Colorado State University. Libraries, 1969)
Over a considerable range of stocking, volume growth per acre is produced in nearly equal amounts. Below the lower end of this range the site is not fully utilized and above the upper limits of this range the stand is stagnated and optimum growth is not realized. This study developed a method for defining the optimum range of stocking for lodgepole pine (Pinus contorta Dougl.) in Colorado and southern Wyoming. The procedure for defining the upper limit of the stocking range was based upon basal area growth rate per tree as a function of stand density. An extension of this relationship provided a curve of basal area growth per acre over stand density for each diameter class. These curves revealed the density at which the peak of basal area growth rate occurred for each class. Basal aera per acre at the peak of basal area growth, when curved over the corresponding stand density for each diameter class, formed the upper limit of the "full-stocking" range. The second part of the study, the establishment of minimum stocking levels for full site occupancy, consisted of an analysis of open-grown trees. It was reasoned that competition between trees. It was reasoned that competition between trees begins at a point where the available growing space in a stand is just equal to the total open-grown, tree-area requirements of all the trees in the stand. The relationship between crown area and diameter breast height was established for the diameters involved. Dividing the area of one acre by the crown area of a tree of a given diameter provided the theoretical number of open-growth trees of this size that could fully occupy the site. The basal area per acre represented by this number of trees was next calculated. The curve delimiting the lower end of the desirable stocking range was then constructed by plotting basal area per acre over the corresponding number of trees per acre. A procedure was developed by which the change in stocking over time might be estimated for use with the established stocking range. This part of the study involved a graphical solution based upon the diameter-age relationship. A rate of change curve was developed for each of three density classes. The full stocking range, as developed in this study, can be used as a guide to the silvicultural needs of a stand. Two stand parameters, average tree diameter and number of trees per acre, are needed to determine the basal area per acre required to fall within the acceptable stocking range. Through the use of these stocking curves, management decisions can be based upon definite guidelines instead of subjective judgements concerning the stand stocking situation.
Covers not scanned. Item deaccessioned after digitization.
Keywords: Lodgepole pine; Forests and forestry; Measurement